Toponīmiskas izcelsmes uzvārdi Latvijā: sastatāmais aspekts - Balodis, Pauls (Baltistica, 2005)
LATVIAN SURNAMES OF TOPONYMIC ORIGIN: A COMPARATIVE ANALYSISThis article is devoted to the question of the origin of Latvian surnames in comparison with personal names in the neighbouring languages – Estonian, Finnish, Lithuanian, Polish, Russian, and German. It is well known in onomastics in general that surnames usually are derived from appellatives and from personal or place names. Since the Latvian system of personal names is rather new, the majority of surnames of Latvian origin are coined on the basis of Latvian appellatives with various meanings. There are many fewer surnames coined from other personal names (there are rather few surnames of patronymic origin). The surnames, which can be supposed to be of toponymic origin (related to concrete geographical objects) are also few in number. But actually it is very difficult to recognize them, because semantically they are very close to the surnames the primary denotation of which is location. Primary personal names derived from place names denote: place from which a person comes; place where a person lives; or place where a person owns property. This type of Latvian personal names has been known from as far back as the 15th-16th centuries. Nowadays there are Latvian surnames coined from Latvian estate names, hydronyms, and a very few from the names of foreign geographical objects. Most often the place name with Ø affixation or with a suffix becomes a surname. Moreover, suffixes denoting inhabitants (-nieks, -ietis) are used in the derivational process.Comparison with other neighbouring languages shows that the situation with regard to surnames is similar also in Estonian and Finnish. It seems that in Finnish the most common way of deriving surnames is from place names.
Keywords: latvių kalba; onomastika; pavardės